2022
DOI: 10.3389/fcell.2022.929288
|View full text |Cite|
|
Sign up to set email alerts
|

FBXO38 Ubiquitin Ligase Controls Centromere Integrity via ZXDA/B Stability

Abstract: Alterations in the gene encoding the E3 ubiquitin ligase substrate receptor FBXO38 have been associated with several diseases, including early-onset motor neuronopathy. However, the cellular processes affected by the enzymatic action of FBXO38 are not yet known. Here, we identify the zinc finger proteins ZXDA/B as its interaction partners. FBXO38 controls the stability of ZXDA/B proteins via ubiquitination and proteasome-dependent degradation. We show that ZXDA/B proteins associate with the centromeric protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…We pretreated the cells with (MLN4924) to avoid the degradation of PD-1, which could be potentially caused by FBXO38 overexpression. Consistent with our previous observations 3,4 , FBXO38 interacted with its substrate ZXDB, and deletion of either its C-terminus or its F-box motif disrupted this interaction (Fig. 1b).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…We pretreated the cells with (MLN4924) to avoid the degradation of PD-1, which could be potentially caused by FBXO38 overexpression. Consistent with our previous observations 3,4 , FBXO38 interacted with its substrate ZXDB, and deletion of either its C-terminus or its F-box motif disrupted this interaction (Fig. 1b).…”
Section: Resultssupporting
confidence: 92%
“…Meng et al overexpressed FBXO38 in HEK293FT cells to enhance PD-1 degradation. However, we have previously shown that FBXO38 overexpression does not result in forced degradation of its substrate 3 . Accordingly, we observed only a modest decrease in ZXDB protein level and no changes in PD-1.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations